2001
DOI: 10.1152/ajpregu.2001.280.3.r612
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic Na+-dependentl-alanine transport in the lizard duodenum. Involvement of systems A and ASC

Abstract: L-Alanine transport across the isolated duodenal mucosa of the lizard Gallotia galloti has been studied in Ussing chambers under short-circuit conditions. Net L-alanine fluxes, transepithelial potential difference (PD), and short-circuit current (Isc) showed concentration-dependent relationships. Na(+)-dependent L-alanine transport was substantially inhibited by the analog alpha-methyl aminoisobutyric acid (MeAIB). Likewise, MeAIB fluxes were completely inhibited by L-alanine, indicating the presence of system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…As has been reported several times for this same preparation (Gómez et al, 1986;Lorenzo et al, 1989b), no differences were observed between the transmural potential difference (PD), short-circuit current (Isc) and tissue conductance (Gt) between stable open-circuit and short-circuit measurements. As can be seen in Table·1, under control conditions, transepithelial PD was approximately 2.0·mV and the mean Isc was 0.77·µequiv.·cm -2 ·h -1 , the serosal side of the tissue being electrically positive compared with the luminal side, which parallels our previous observations (Gómez et al, 1986;Medina et al, 2001). Both PD and Isc were significantly increased by forskolin, theophylline and db-cAMP, in agreement with most studies performed in different animal models, including lizard intestine (Bridges et al, 1983;Díaz and Lorenzo, 1991;Lorenzo et al, 1989a).…”
Section: Effects Of Forskolin Theophylline and Db-camp On Totalsupporting
confidence: 87%
See 4 more Smart Citations
“…As has been reported several times for this same preparation (Gómez et al, 1986;Lorenzo et al, 1989b), no differences were observed between the transmural potential difference (PD), short-circuit current (Isc) and tissue conductance (Gt) between stable open-circuit and short-circuit measurements. As can be seen in Table·1, under control conditions, transepithelial PD was approximately 2.0·mV and the mean Isc was 0.77·µequiv.·cm -2 ·h -1 , the serosal side of the tissue being electrically positive compared with the luminal side, which parallels our previous observations (Gómez et al, 1986;Medina et al, 2001). Both PD and Isc were significantly increased by forskolin, theophylline and db-cAMP, in agreement with most studies performed in different animal models, including lizard intestine (Bridges et al, 1983;Díaz and Lorenzo, 1991;Lorenzo et al, 1989a).…”
Section: Effects Of Forskolin Theophylline and Db-camp On Totalsupporting
confidence: 87%
“…L-alanine transport The effects of different pharmacological agents affecting cAMP metabolism on unidirectional and net fluxes of L-alanine (1·mmol·l -1 ) across the isolated lizard duodenum have been determined under short-circuit conditions (Fig.·1). Using Na + -containing Ringer solutions, mean control net L-alanine transport (Jnet) was 14.81±1.05·nmol·cm -2 ·h -1 (significantly different from zero at P<0.01), which was in the range reported previously for this same preparation (Medina et al, 2001). Addition of forskolin (10·µmol·l -1 ), theophylline (3·mmol·l -1 ) or the membrane-permeable analogue dibutyryl cyclic AMP (db-cAMP; 500·µmol·l -1 ) significantly increased Jnet, these effects being due to a rise in the mucosal-to-serosal flux (Jms) without altering the flux in the opposite direction (Jsm).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations